Framing the reaction of President Abbas on the issue of moving the US Embassy from Tel Aviv to Jerusalem - Arandas, Mohammed Fadel; Chang, Peng Kee; Mohamad, Emma Mirza Wati; Idid, Syed Arabi (Universiti Kebangsaan Malaysia Press, 2018)
The study has examined the similarities and differences in the coverage of two Palestinian news agencies Ma’an and Palestinian Information Center (PIC) on the reactions of Palestinian President Mahmoud Abbas’s regarding relocating the US embassy from Tel Aviv to Jerusalem. The study has also aimed to explore the use of four function of framing by Entman 1993 in the news stories of both agencies. Qualitative content analysis has been adopted to achieve the aim of this study. The total sampling number was 9 news stories; 3 stories have been retrieved from Ma’an, and the other 6 have been retrieved from PIC. The time frame has started from December 5, 2017 which marked the day of informing Abbas by Trump’s decision to move the Embassy until December 22 2017 which was a day after gaining a sweeping victory in UN by President Abbas through a resolution that rejected the decision. Both of the news agencies were supportive to President Abbas in their coverage and none of them has any negative coverage about him. From the sampling number it can be seen that PIC has paid more attention for the coverage of this issue than Ma’an. However, PIC has ignored the success of President Abbas for achieving UN resolution against Trump’s decision. Morover, all the news stories has included “define the problem” while excluded “diagnose causes” functions. However both “make moral judgment” and “suggest remedies” have been included in all news stories of Ma’an, and only half of news stories of PIC.